Pembelajaran Pada Anak Tuna Grahita di SDLB Negeri Keleyan Bangkalan - tridayanti, ciyana; Harsiwi , Nova Estu (ALENA : Journal of Elementary Education, 2024)
The aim of this research is to obtain an overview of the implementation of learning for mentally retarded students in special schools. Special education for children with special needs includes learning for students who have disabilities or students who have extraordinary intelligence, one of whom is mentally retarded. This research uses a descriptive method using a qualitative approach. Data collection techniques include interviews, observation, and documentation. The results of the research show that the learning preparation carried out by the school is quite good because it is carried out in accordance with its function, and the implementation of learning for mentally retarded children is appropriate, where in the special school there is also a special development program for mentally retarded students.